2015
DOI: 10.1002/joc.4295
|View full text |Cite
|
Sign up to set email alerts
|

Projections of aridity and its regional variability over China in the mid‐21st century

Abstract: ABSTRACT:The effects of aridity on ecosystems and water cycles are pronounced and have received considerable attention. However, aridity changes due to future warming and its regional variability over China remain uncertain. This paper aims to identify the spatiotemporal variations in aridity and its key influencing factors over China in the mid-21st century based on five general circulation models (GCMs) and four representative concentration pathway (RCP) scenarios. An aridity index (AI), defined as the ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 65 publications
(85 reference statements)
3
29
1
Order By: Relevance
“…This kind of drying mechanism is consistent with that suggested in assessments dealing with changes in surface dryness during the 20th and 21st centuries using reconstructed data and future climate projections (Sherwood and Fu, 2014). Thus, our study might reflect an observed precursor of the projected drying trends over the humid areas in 21st century (Cook et al, 2014;Yin et al, 2015). The present results also indicate that drying of the land surface in response to warming is already in progress, not simply a future risk.…”
Section: Discussionsupporting
confidence: 91%
“…This kind of drying mechanism is consistent with that suggested in assessments dealing with changes in surface dryness during the 20th and 21st centuries using reconstructed data and future climate projections (Sherwood and Fu, 2014). Thus, our study might reflect an observed precursor of the projected drying trends over the humid areas in 21st century (Cook et al, 2014;Yin et al, 2015). The present results also indicate that drying of the land surface in response to warming is already in progress, not simply a future risk.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, the climate simulation datasets used in this study were obtained from the ISI-MIP, which have been bias-corrected in the fasttrack of ISI-MIP using the trend-preserving method and can reproduce the observed climate very well [35]. Several studies have demonstrated the value of using the same projections by the 5 GCMs in climate change impact assessments for different sectors at the global and regional scales [50][51][52][53][54].…”
Section: Climate Model Uncertaintymentioning
confidence: 99%
“…The surface air temperature in Chinese land increases in the 21st century under all the RCPs (Yin et al, 2015). Based on their positive sensitivities to temperature change, the national average GDD and GS in the long term are 279.1 CÁd higher and 16.5 days longer for RCP 2.6 and 964.4 CÁd higher and 50.3 days longer for RCP 8.5, relative to the present day.…”
Section: Future Changes In Gdd and Gsmentioning
confidence: 99%